An Assessment of Coleopteran Fauna of The Forest of Siswan, Punjab - Singh, Amar Paul; Mahajan, Shagun; De, Kritish; Uniyal, V. P.; Bhardwaj, A. K. (Indian Forester, 2019)
The present paper provides the result of assessment of coleopteran fauna of forest of the forest of Siswan, Punjab. A total of 43 species belonging to 32 genera and 12 families were identified. Out of these 12 families, family Scarabaeidae (dung beetles) was dominant (with 20 species), followed by family Chrysomelidae (leaf beetles, 4 species) and family Coccinellidae (ladybird beetles, 3 species) and family Meloidae (Blister beetles, 3 species. All the taxa are reported from the area for the first time.